2015
DOI: 10.5049/ebp.2015.13.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Salt Sensitivity and Hypertension: A Paradigm Shift from Kidney Malfunction to Vascular Endothelial Dysfunction

Abstract: Hypertension is a complex trait determined by both genetic and environmental factors and is a major public health problem due to its high prevalence and concomitant increase in the risk for cardiovascular disease. With the recent large increase of dietary salt intake in most developed countries, the prevalence of hypertension increases tremendously which is about 30% of the world population. There is substantial evidence that suggests some people can effectively excrete high dietary salt intake without an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 61 publications
1
64
0
6
Order By: Relevance
“…Notwithstanding, recent studies indicate that modification of endothelial cell function and non-osmotic storage of salt could be the result of changes in endothelial surface layer characteristics. Therefore, it seems that, in addition to kidney malfunction, endothelial dysfunction could be considered as an effective factor related to salt sensitivity and sodium homeostasis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, recent studies indicate that modification of endothelial cell function and non-osmotic storage of salt could be the result of changes in endothelial surface layer characteristics. Therefore, it seems that, in addition to kidney malfunction, endothelial dysfunction could be considered as an effective factor related to salt sensitivity and sodium homeostasis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Alta ingesta de sodio, (excreción> 6g Na/día) Baja ingesta de sodio, (excreción <3g Na/día) (La reducción de la ingesta, solo aplicada a pacientes con HAS y dieta alta en Na). Sin embargo, diversos estudios han demostrado que no en todos los individuos un consumo de sal elevado se asocia con hipertensión (Young, C. H. et al, 2015), ni tampoco todos los sujetos responden de igual forma a la reducción de ingesta de sodio. Se ha sugerido que una dieta baja en sodio (3 g de sal Na/ d) podría ser más eficaz en la reducción de la PA en mujeres y ancianos (He, F. J. et al, 2009) y en sujetos de raza negra o asiática en comparación con la caucásica (Graudal N.A., 2012).…”
Section: Estudiosunclassified
“…Los mecanismos subyacentes que promueven esta variabilidad son complejos y van desde la genética hasta influencias ambientales (Young, C. H., 2015).…”
Section: Estudiosunclassified
“…In addition to these, dietary sodium, or salt, intake has been found to play a key player, and the most common and important risk factor for hypertension. [3] Numerous clinical trials have shown a direct association and causal relation between salt intake and the pathogenesis of hypertension. In particular, sodium retention due to the overproduction of sodium-retaining hormones or inappropriate renal salt handling due to alterations in expression of the Kallikrein-Kinin system have been implicated as mechanisms in hypertension.…”
Section: Introduction the Evolving Understanding Of Salt And Hypertenmentioning
confidence: 99%